Frequency of lucid dreaming in a representative German sample - Schredl, Michael; Erlacher, Daniel (Perceptual and motor skills, 2011)
Lucid dreams occur when a person is aware that he is dreaming while he is dreaming. In a representative sample of German adults (N = 919), 51% of the participants reported that they had experienced a lucid dream at least once. Lucid dream recall was significantly higher in women and negatively correlated with age. However, these effects might be explained by the frequency of dream recall, as there was a correlation of .57 between frequency of dream recall and frequency of lucid dreams. Other sociodemographic variables like education, marital status, or monthly income were not related to lucid dream frequency. Given the relatively high prevalence of lucid dreaming reported in the present study, research on lucid dreams might be pursued in the sleep laboratory to expand the knowledge about sleep, dreaming, and consciousness processes in general.
Gesehen am 26.10.2022